How Hispanic patients address ambiguous versus unambiguous bias in the doctor's office. Issue 11 (13th May 2014) - Bean, Meghan G.; Covarrubias, Rebecca; Stone, Jeff
Abstract Two studies examined Hispanic individuals' preferences for using ten different bias reduction strategies when interacting with a doctor whose beliefs about their group were either ambiguous or clearly biased. Consistent with predictions, participants who imagined interacting with a doctor whose beliefs were ambiguous preferred strategies that facilitate positive doctor–patient interactions, whereas participants whose doctor explicitly endorsed negative stereotypes about their group preferred strategies that address stereotype content. The results also revealed that, regardless of whether the doctor's beliefs were ambiguous or clearly biased, stigma consciousness predicted participants' preferences for using strategies that address stereotype content. These findings suggest that both doctors' behavior and individual‐level factors influence how minority individuals choose to behave in a healthcare setting.